Pop Art 1956-1968 - Guadagnini, Walter; Hegyi, Lóránd; Lancioni, Daniela (Milano : Silvana Editoriale, 2007)
Angeli, Franco ; Arman ; Artschwager, Richard ; Axell, Evelyne ; Baj, Enrico ; Blake, Peter ; Boshier, Derek ; Caulfield, Patrick ; Ceroli, Mario ; Christo ; D'Arcangelo, Allan ; Dine, Jim ; Donaldson, Anthony ; Equipo Cronica ; Errò ; Fahlström, Öyvind ; Festa, Tano ; Fioroni, Giosetta ; Gilli, Claude ; Hains, Raymond ; Hamilton, Richard ; Haworth, Jann ; Hockney, David ; Indiana, Robert ; Jacquet, Alain ; Jess ; Johns, Jasper ; Johnson, Ray ; Jones, Allen ; Kitaj, R.B. ; Laing, Gerald ; Lakner, Laszlo ; Lichtenstein, Roy ; Lombardo, Sergio ; Mauri, Fabio ; Monory, Jacques ; Oldenburg, Claes ; Paolozzi, Eduardo ; Pascali, Pino ; Phillips, Peter ; Pistoletto, Michelangelo ; Raffaele, Joe ; Ramos, Mel ; Rancillac, Bernard ; Rauschenberg, Robert ; Raysse, Martial ; Richter, Gerhard ; Rivers, Larry ; Rosenquist, James ; Rotella, Mimmo ; Ruscha, Ed ; Schifano, Mario ; Segal, George ; Spoerri, Daniel ; Stämpfli, Peter ; Stevenson, Harold ; Thiebaud, Wayne ; Tilson, Joe ; Warhol, Andy ; Wesselmann, Tom
Pop Art 1956-1968, Scuderie del Quirinale Roma, 2007-10-26. 2008-01-27
boek